Influence of work material, cutting conditions and rigidity of tool holders on machine tool chatter - Amin, A. K. M. Nurul (1992)
Experimental investigation have been carried out to determine the influence of job materials, cutting speed and stiffness of tool holder on chatter phenomenon which arises during metal cutting operation. Experiments were performed on Engine Lathe of model Celtic-14. Medium Carbon Steel Stainless Steel, Cast Iron and Brass were taken as work materials. Cemented Carbide containing 92% WC and 8% Co was taken as cutting tool material. Three different tool holders having different cross¬ sectional areas and, mechanical clamping arrangement for tool bits, were used. An experimental set-up, consisting of a function generator, amplifiers, vibrator head, pressure transducer, oscilloscope and camera were used for determining the natural frequency of the different elastic elements, including the tool holders. Frequency and amplitude of vibration and chatter were determined by two methods - by using the above mentioned experimental set-up and by measuring the average distance between two vibration marks on job surface or between two chip elements using an instrumental microscope.